The Architecture of Oppression : the SS, Forced Labor and the Nazi Monumental Building Economy. - Jaskot, Paul B. (Architext., 2002)
This book re-evaluates the architectural history of Nazi Germany and looks at the development of the forced-labour concentration camp system. Through an analysis of such major Nazi building projects as the Nuremberg Party Rally Grounds and the rebuilding of Berlin, Jaskot ties together the development of the German building economy, state architectural goals and the rise of the SS as a political and economic force. As a result, The Architecture of Oppression contributes to our understanding of the conjunction of culture and politics in the Nazi period as well as the agency of architects and SS.